Predicciones de la relación altura - diámetro en plantas de Simarouba amara Aubl. "marupa" en bosque natural y en plantación, Puerto Almendra, Loreto, Perú - 2021 - Shapiama Peña, Rony Fernando (2022)
The study was carried out in the “El Huayo” Arboretum and in a CIEFOR Puerto Almendra - FCF - UNAP plantation, San Juan Bautista district, Maynas province, Loreto region. The objective was to know the diameter-total height relationship in the Simarouba amara Aubl plants. "marupa" in natural forest and plantation. As variables, the diameter (dbh) and total height of the trees of the species under study with DAP ? 10 cm (Arboretum “El Huayo”) and of the plantation were considered. The results show that in the relation diameter - total height in the plants of Simarouba amara Aubl. "Marupa" in natural forest, 2 allometric models with the best fit, the quadratic and the cubic, were defined; It also presented a good relationship between the variables evaluated; Regarding the plantation, the allometric model that had the best adjustment was power, with an excellent degree of relationship between diameter and total height of the plants.